PP.LB02.10: CARDIOPROTECTIVE ROLE OF ZOFENOPRIL IN HYPERTENSIVES WITH ACUTE MYOCARDIAL INFARCTION. (June 2015) - Borghi, C.; Omboni, S.; Reggiardo, G.; Bacchelli, S.; Esposti, D. Degli; Ambrosioni, E.
Abstract : Objective: The SMILE (Survival of Myocardial Infarction Long-term Evaluation) studies demonstrated that early administration of zofenopril following acute myocardial infarction (AMI) is prognostically beneficial compared to placebo or other angiotensin-converting enzyme inhibitors (ACE-inhibitors). In the present meta-analysis of individual data of four SMILE studies we evaluated the cumulative efficacy of zofenopril on cardiovascular (CV) morbidity and mortality in the subgroup of hypertensive patients. Design and method: 1880 (53.1%) of the 3542 patients had a positive history for hypertension. 449 hypertensives and 486 normotensives were treated with placebo (SMILE 1 and 3), 980 and 786 with zofenopril 30–60 mg/die (all four studies), 451 and 390 with lisinopril 5–10 mg/die (SMILE 2) or ramipril 10 mg/die (SMILE 4). Treatment was continued for 6 to 48 weeks. For the purpose of this pooled analysis the primary study endpoint was set to 1-year combined occurrence of death or hospitalization for CV causes. Results: The risk of CV events was significantly reduced by 35% with zofenopril vs. placebo [HR: 0.65; 95% CI: 0.49–0.86; p = 0.003) in hypertensive patients and by 41% in normotensive patients (0.59; 0.44–0.79; p = 0.0001). The other ACE-inhibitors reduced CV morbidity and mortality as well, though the reduction (−17%) was not statistically significant vs. placebo either in hypertensives (0.83; 0.57–1.21; p = 0.338) or normotensives (reduction: −24%; HR: 0.76; 0.50–1.15; p = 0.194). Treatment with zofenopril of hypertensive and normotensive patients was associated with a non-statistically significant reduction in the risk of CV outcomes as compared to the other ACE-inhibitors (hypertensives: 0.78; 0.60–1.01; p = 0.062; normotensives: 0.77; 0.55–1.10; p = 0.1509). Conclusions: In high-risk cardiac patients with arterial hypertension, zofenopril treatment is associated with a clinically relevant reduction in long-term CV morbidity and mortality, compared to placebo, with an efficacy similar to that of other ACE-inhibitors, such as lisinopril and ramipril.